2007
DOI: 10.1038/sj.ejcn.1602963
|View full text |Cite
|
Sign up to set email alerts
|

Multivitamin supplementation improves nutritional status and bone quality in aged care residents

Abstract: Objectives: To assess the effectiveness of a multivitamin (MV) tablet on nutritional status, quantitative heel ultrasound (QUS), mobility, muscle strength and falls. The design comprised two groups matched on mobility levels, randomized to receive a daily MV or placebo (P) tablet for 6 months. The setting was an Australian residential care facility. Subjects: A total of 92 aged care residents. Serum micronutrients, body weight, QUS, rate of falls, hand grip strength, and the timed up and go test were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 27 publications
2
34
0
2
Order By: Relevance
“…A 4% incidence of B12 deficiency indicates that B12 status is a relevant form of malnutrition in this population. Yet, the present study provides evidence that B12 status is amenable to treatment, which is consistent with extant literature on intervention studies (Baker et al 1980;Wouters-Wesseling et al 2002;Grieger et al 2009;Rozgony et al 2010;Favrat et al 2011). Whether this remains true for older adults after admission to LTC remains unknown and further evidence for burden of illness and establishing causality of improved B12 status on clinical outcomes is warranted.…”
Section: Discussionsupporting
confidence: 76%
“…A 4% incidence of B12 deficiency indicates that B12 status is a relevant form of malnutrition in this population. Yet, the present study provides evidence that B12 status is amenable to treatment, which is consistent with extant literature on intervention studies (Baker et al 1980;Wouters-Wesseling et al 2002;Grieger et al 2009;Rozgony et al 2010;Favrat et al 2011). Whether this remains true for older adults after admission to LTC remains unknown and further evidence for burden of illness and establishing causality of improved B12 status on clinical outcomes is warranted.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, our finding is consistent with previous studies that have yielded positive or at least encouraging data supporting the use of biologically based therapies (e.g., vitamins and minerals) and better functional status. 20,21 This analysis also found that the use of manipulative and body-based therapies predicts better functional status, better physical HRQoL, and better mental-health related quality of life. Manipulative and body-based therapies include chiropractic and massage therapy.…”
Section: Discussionmentioning
confidence: 77%
“…Nine trials (584 participants) provided 12 comparisons of two different exercise programmes (Faber 2006; Fu 2015; Imaoka 2016; Kovacs 2012; Saravanakumar 2014; Shimada 2004; Serra-Rexach 2011; Sitja Rabert 2015; Tuunainen 2013). All trials were individually randomised.…”
Section: Resultsmentioning
confidence: 99%